1970
DOI: 10.1139/z70-188
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of mice to Toxocara canis: effect of prechallenge infections and injections of worm extracts

Abstract: Test mice have been infected one or more times and challenged with Toxocara canis larvae in an attempt to demonstrate acquired resistance to this nematode in a paratenic host. The worm burden of these mice at necropsy was not significantly less than that for controls.Mice given prechallenge injections of somatic fractions of T. canis eggs and adult worms, together with adjuvant, were found to harbor significantly fewer larvae after a challenge infection than did controls. The worm burden of mice similarly inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Published reports differ in whether protection against reinfection was obtained in such experiments (Olson, 1962) or not (Schmunis andPacheco. 1970: Izzat andOlson, 1970), but any such protection was limited, if it occurred at all. Extracts from worms gave better protection (Izzat and Olson, 1970).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published reports differ in whether protection against reinfection was obtained in such experiments (Olson, 1962) or not (Schmunis andPacheco. 1970: Izzat andOlson, 1970), but any such protection was limited, if it occurred at all. Extracts from worms gave better protection (Izzat and Olson, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…1970: Izzat andOlson, 1970), but any such protection was limited, if it occurred at all. Extracts from worms gave better protection (Izzat and Olson, 1970). As in our experiments, immunisation delays migrating larvae in the liver (Olson, 1962).…”
Section: Discussionmentioning
confidence: 99%
“…To date, attempts to generate protective anti-larval immunity in laboratory rodents have had mixed results. While an early report noted that immunisation with somatic extracts of eggs or adult worms resulted in approximately half the number of surviving challenge larvae (Izzat and Olson, 1970), susceptibility to larval infection was unaltered in mice immunised with UV-irradiated eggs or larval ES antigens (Abo-Shehada et al, 1991). Likewise, a more recent study found no evidence of protection by administering a second challenge of larvae to previously infected mice, other than they were more likely to sequester in the brain (Kolbeková et al, 2011).…”
Section: Immunity In the Definitive Hostmentioning
confidence: 99%
“…Recently we examined the impact of single versus multiple exposures to T. canis (4). In this situation, we anticipated a more heightened and sustained host immune reaction to secondary and subsequent infections of the parasite (44)(45)(46)(47)(48)(49)(50). Prior work had noted that the pattern of larval distribution in various organ systems is different in rodents given single versus multiple doses of T. canis (51)(52)(53).…”
Section: Immunological Considerationmentioning
confidence: 99%